Identification of the gene encoding an RNA polymerase-binding protein of bacteriophage T4. - Williams, K P (1987)
One of five bacteriophage T4-specified proteins that bind to host RNA polymerase core has been purified and partially sequenced. A mixed oligonucleotide, based on the amino acid sequence, was used to probe genomic restriction fragments. The gene for this protein, previously designated the 15K protein, has been located between T4 genes 45 and 46 and designated rpbA.